2018
DOI: 10.1093/ecco-jcc/jjy046
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-590-5p Inhibits Intestinal Inflammation by Targeting YAP

Abstract: Our results suggest that miR-590-5p inhibits intestinal inflammation in mouse colon and tumourigenesis of colorectal cancer cells by inhibiting YAP. The miR-590-5p/YAP axis may be an important novel mechanism in the pathogenesis of CD and colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…In particular, previous literature has reported that YAP is crucial for epithelial progenitor cell proliferation and differentiation, and is involved in epithelial repair 123 . YAP mRNA is significantly upregulated in IECs in patients with CD and mice with colitis 47 . In the DSS-induced colitis and regeneration models, YAP is overexpressed and colonic epithelial cells in crypts actively proliferate 8,43 .…”
Section: Hippo and The Pathophysiology Of Ibd-associated Colitis Hippmentioning
confidence: 97%
See 2 more Smart Citations
“…In particular, previous literature has reported that YAP is crucial for epithelial progenitor cell proliferation and differentiation, and is involved in epithelial repair 123 . YAP mRNA is significantly upregulated in IECs in patients with CD and mice with colitis 47 . In the DSS-induced colitis and regeneration models, YAP is overexpressed and colonic epithelial cells in crypts actively proliferate 8,43 .…”
Section: Hippo and The Pathophysiology Of Ibd-associated Colitis Hippmentioning
confidence: 97%
“…Increasing research in recent years has indicated an interplay between the Hippo and other pathways in intestinal regeneration, including the WNT 43 and Notch 44 pathway. Furthermore, the Hippo pathway has been suggested to be associated with inflammation, including the NF-κB pathways 45,46 and other components 9,47 , and also with immune-regulating pathways 15 .…”
Section: Interplays Between the Hippo Signalling And Other Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-590-5p was described as part of a six-miRNA panel that reflects the response to chemoradiotherapy (48). One target of the miR-590-5p is Yes associated protein (YAP) (49), which induces cell growth and invasion in BC (50). Overexpression of YAP is partly responsible for poor prognosis in BC (50,51).…”
Section: Validation Cohort N=36 -------------------------------------mentioning
confidence: 99%
“…6 Increasing evidence suggests that miRNAs are widely dysregulated in UC, potentially impacting UC pathogenesis, diagnosis and therapy. [6][7][8] For example, Wu et al found that miR-206 regulates TNF-α and IL-8 in active human UC and dextran sodium sulphate (DSS)-induced experimental colitis in mice. 8 Min et al illustrated that miR-155 overexpression enhanced UC inflammatory activity by down-regulating the expression of FOXO3a, a key inhibitor of the NF-κB signalling pathways.…”
Section: Introductionmentioning
confidence: 99%